Enhancing WLAN Performance with Rate Adaptation Considering Hidden Node Effect - Chang-Woo Ahn; Sang-Hwa Chung (International Journal of Distributed Sensor Networks)
In IEEE 802.11 WLANs, many rate adaptation studies have proposed rate adaptation schemes to differentiate channel-related loss and collision loss in order to enhance WLAN performance. Most of these studies focus on rate adaptation schemes on the client side when many clients transmit uplink traffic to an access point (AP). However, considering the high proportion of downlink traffic in WLANs, rate adaptation on the AP side has a greater impact on WLAN performance and is more influenced by the downlink traffic on neighboring APs. In addition, considering that many APs are deployed in the real world, some APs use the same channel and are hidden from each other. In this paper, we first analyze the impact of hidden nodes on the rate adaptation scheme. We then propose a new rate adaptation scheme, called Hidden node Effect aware Rate Adaptation (HERA). HERA optimizes the RTS exchange by utilizing RTS transmission success/failure and makes rate decrease decisions based on frame error rate (FER) in order to enhance WLAN performance. We evaluate the performance of HERA through extensive simulation, comparing it with other well-known rate adaptation schemes. Simulation results show that HERA outperforms other rate adaptation schemes by up to 161% in terms of downlink throughput in hidden node environments.